Taliban di Afghanistan: Tinjauan Ideologi, Gerakan dan Aliansinya dengan ISIS - Ashghor, Aly (Jurnal Keamanan Nasional, 2021)
This article aims to describe the ideology and movement of the Taliban in Afghanistan. The question posed in this article revolves around what is the ideology of the Taliban. Where did the term Taliban come from? Why is it easy for the Taliban to establish cooperation with al-Qaeda and ISIS? Therefore, by describing the transformation of the Taliban jihad movement from the era of the Soviet-Afghan war to the birth of the Taliban Regime, this article provides a conclusion that local conflicts in Afghanistan gave birth to the landscape of the global terrorism movement that had an impact on the development of terrorism in Indonesia.